Заметки по иудейской эпиграфике Мангупа - Кашовская, Н.В. (Материалы по археологии, истории и этнографии Таврии, 2003)
Из эпиграфического собрания крымских еврейскоязычных памятников интерес вызывают эпитафии с датировками, которые имеют конкретное значение для определения времени появления могильников. Для кладбища Табана-Дере одной из таких надписей является эпитафия с именем “Ефросиния. From the epigraphic collection of Crimean monuments with inscriptions in the Jewish language epitaphs with dates are of concrete importance for dating the emergence of cemeteries. For the cemetery of Tabana-Dere one of such inscriptions is the epitaph with the name of “Euphrosyne”. In two different in period of composition and publication collections of epitaphs from this cemetery the mentioned gravestone records one date 5147 (1387), but it marked by different catalogue numbers - № 28 [5, P.213] and N 1 [7, P. 14]. Such location in catalogues reflected conceptual positions of two authors. Subsequent publications concerning the cemetery directly or indirectly broached only appreciation of authors. It was only in the 90s of the 2nd century when it became possible to realize the necessity to investigate the cemetery again.